O1-S11.04 Targeting the use of HIV RNA screening to maximise yield and minimise cost: NYC Health Department STD Clinics, 2008–2010. (10th July 2011) - Blank, S; Borges, C; Kowalski, A; Sebiyam, S; Sweeney, M
Abstract : Background: Nucleic acid amplification testing (NAAT) is an important tool for identifying acute HIV infection (AHI), a period of high infectivity when antibody is undetectable. NAAT pooling methods (pNAAT) help contain the costs of screening for AHI. In 2008 NYC STD clinics began routine pNAAT screening for all rapid antibody negative specimens; it was standard of care in all nine clinics by 2009. A pattern of risk factors among AHI cases detected during universal screening suggested the feasibility of using targeted screening to maximise the yield of AHI cases detected while minimising costs of screening. Methods: Using medical record data, we reviewed cases of AHI diagnosed in nine NYC STD clinics for 2008–2009. From these we developed targeting criteria for AHI screening, and compared yields and costs before and after targeting.was implemented. Results: Targeted screening began in May 2010 and included the following risk criteria: MSM, females who have had sex with MSM, sex with an injection drug user, exchange sex for money or drugs, shared injection drug works, or recent victim of sexual assault. Prior, 42 696 specimens were screened by pNAAT from June through December 2009, yielding 23 AHI cases (5.4 cases/10 000 specimens). Of these cases, there were 21 males, including 15 who have sex with men (MSM) (71%, 15/21), 1 female, and 1 transgender. The mean age for patients was 30 years; racial/ethnic breakdown was: 57% Black, 39% Hispanic, 13% white, 4% other. Subsequently, 5280 specimens were screened by pNAAT from June through December 2010, representing an 88% decrease in testing compared to the same period during the previous year. A total of 18 AHI cases (34.1/10 000 specimens) were detected; all were MSM. The mean age was 29 years and racial/ethnic breakdown was: 44% Black, 28% Hispanic, 28% white, 5% Asian. Cost data are provided in Abstract O1-S11.04 table 1 . Conclusion: AHI screening increases case detection compared to using antibody tests alone. After initial investment in the effort, we were able to cut the cost per case identified by over sevenfold. This approach may make AHI screening more feasible/affordable in settings with patients at very high risk of newly-acquiring HIV.